Fysioterapeuters erfaringer med bruk av fysisk aktivitet til eldre deprimerte - Anne Margrethe Ulleberg; Berit Johannesen (Septentrio Academic Publishing, 2015)
This article is based upon a study of the experiences of physiotherapists working with elderly depressed patients and the use of physical activity. Depression in the elderly is a common condition, and it is estimated to be the second most common cause of failing health towards 2020. Physical activity has a positive effect on depression in the elderly. The aim of this study was to investigate the experiences of physiotherapist`s in the treatment of elderly depressed patients over 65 years of age. Data was collected by qualitative reasearch interviews of 5 physiotherapists. Important findings of this study were that the physiotherapists experienced that they did not get any referrals to treatment solely due to depression, and that they needed a different approach to physical activity compared to other patient groups.